The temptation to be happy - Marone, Lorenzo, 1974-; Whiteside, Shaun (London, England : Oneworld, 2017)
When Emma moves into his apartment building, Cesare, a elderly widower and troublemaker, finds himself risking everything for a future he never thought possible.
Keywords: Widowers -- Fiction; Apartment dwellers -- Fiction; Interpersonal relations -- Fiction; Neighbors -- Fiction; Widowers -- Fiction; Apartment houses -- Fiction; Interpersonal relations -- Fiction; Neighborhood -- Fiction; Italy -- Fiction; Italy -- Fiction